2021
DOI: 10.1101/2021.11.19.21266529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on community antibiotic prescribing and stewardship: a qualitative interview study with general practitioners in England

Abstract: The COVID-19 pandemic has had a profound impact on the delivery of primary care services. We aimed to identify general practitioners’ (GPs’) perceptions and experiences of how the COVID-19 pandemic influenced antibiotic prescribing and antimicrobial stewardship (AMS) in general practice in England. Twenty-four semi-structured interviews were conducted with 18 GPs at two time-points: autumn 2020 (14 interviews) and spring 2021 (10 interviews). Interviews were audio-recorded, transcribed and analysed thematicall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Once infected with SARS-CoV-2, they are prone to developing severe or fatal symptoms, associated with higher rates of hospitalization and mortality [ 18 , 19 ]. On this basis, the European and US transplant guidelines consider that the benefits of COVID-19 vaccination may overweigh risks for patients receiving HSCT or CAR T-cell and recommend COVID-19 vaccination as early as three months after transplantation or cell therapy [ 20 , 21 ]. These recommendations were based on limited evidence from individual studies on COVID-19 vaccines with small sample size and previous clinical experience with infections caused by other pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Once infected with SARS-CoV-2, they are prone to developing severe or fatal symptoms, associated with higher rates of hospitalization and mortality [ 18 , 19 ]. On this basis, the European and US transplant guidelines consider that the benefits of COVID-19 vaccination may overweigh risks for patients receiving HSCT or CAR T-cell and recommend COVID-19 vaccination as early as three months after transplantation or cell therapy [ 20 , 21 ]. These recommendations were based on limited evidence from individual studies on COVID-19 vaccines with small sample size and previous clinical experience with infections caused by other pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus Disease-19 (COVID-19) pandemic swept across the world quickly and placed a heavy burden on the health systems globally. The impacts of the COVID-19 pandemic on antibiotic consumption and the risk of AMR have aroused the attention of many researchers of antibiotic resistance [11][12][13][14][15][16][17][18][19]. A report stated that after the outbreak of the COVID-19 pandemic in most European countries, the total consumption of antibiotics declined by more than 15%, which was mainly observed in PHSs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several national studies conducted in the USA, Portugal, Canada, and the UK also showed that a signi cant decrease was observed in the overall antibiotic consumption by outpatients or in broadspectrum antibiotic prescriptions during the COVID-19 pandemic; especially, the number of prescriptions of certain categories of antibacterials (e.g., third-generation cephalosporins, uoroquinolones) decreased signi cantly [11,12,[14][15][16]. In China, a few similar studies also found that there was a decline in consumption of antibiotics during the .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rapid reform has also affected ASP activities, where efforts to resume ASP practices have been described through embracing technology to facilitate ASP meetings and rounds, upgrading existing electronic health systems, increasing use of procalcitonin to differentiate between viral and bacterial infection and increased adoption of outpatient parenteral antimicrobial therapy (OPAT) [1,5]. ASP team members have efficiently contributed to the pandemic relief effort through their roles in novel antiviral clinical trials, COVID-19 disease management guideline development, repurposing prospective audit and feedback, formulary restriction and preauthorisation to support COVID-19 patients [2,10].…”
Section: Introductionmentioning
confidence: 99%